Comparison of the effectiveness of the irrigation material ethyl diamine tetra-acetic acid (edta) 17% and benzalconium chloride 1% on the smear layer in the 1/3 apical - Putra Angkasa, Juliano; Djuanda, Rudy; Tarigan, Gita (Science Midwifery, 2024)
Context: A smear layer can form on the root canal walls during mechanical root canal preparation. Bacteria that cause root canal infections can grow on the smear layer, which can also lead to micro-leakage in the top one-third of the root canal. Benzalkonium chloride (BAC) is a necessary and effective substance for root canal irrigation. In addition to being a cationic nitrogen agent having a quaternary ammonium group, BAC is a combination of alkyl dimethyl benzyl ammonium chloride, which has broad spectrum antibacterial activity. The goal of this study was to assess the efficacy of 1% BAK and 17% EDTA on the smear layer of the apical 1/3 and to measure the degree of cleanliness that BAK produced compared to 17% EDTA. The research was conducted utilising a scanning electron microscope (SEM) approach in a laboratory setting. Findings: SEM analysis of the sample smear layer yielded BAK 1% 0.667 and EDTA 17% 1.667 according to the Garberoglio and Becce scoring system. Kruskal-Wallis analysis of the data showed that the 17% EDTA group had an average range of 11.50, the 1% BAK group of 5.58, the 2.5% NaOCl group of 11.92, and the negative control group of 21.00. In conclusion, when comparing the groups with and without the negative control, the 17% EDTA group had a p value of 0.0069, the 1% BAK group a p value of 0.0019, and the 2.5% NaOCl group a p value of 0.0013, all determined by Mann-Whitney data analysis. Thus, it is evident that BAK 1% is more efficient than EDTA 17% in affecting the smear layer at the apical 1/3.